The Effectiveness of Diabetes Self-Management Education on Changes in Blood Sugar Levels in Type II DM Patients at the Klatak Public Health Center, Banyuwangi Regency - Achmad Efendi; Lidia Hastuti; Wuriani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Providing self-skills education and training to improve the ability of type II DM sufferers to carry out self-care management (DSME) including 8 important components and applying peer support to increase motivation and improve their health, avoid complications to early death. Objective: This study aimed to determine the effectiveness of Diabetes Self-Management Education on changes in blood glucose levels in patients with type II DM at Banyuwangi Regency in 2023. Method: Experimental research with the design of True Experimental Pretest pos-ttest control group design. The population were all type II DM patients who were treated regularly at the Klatak Public Health Center. A sample of 24 respondents in the control and 24 in the intervention groups used the MSD sample size formula. Respondents in this study were examined pre- & post-test venous plasma blood glucose levels. The sampling technique used is an RCT. Data analysis used SPSS 21 for Windows statistical T-test. Result: The paired T-test results indicated that the P-value for the intervention group was less than 0.05, specifically 0.000. It means Ha is accepted. So, the blood glucose levels differ before and after undergoing DSME with the Peer Support Group method. Then, with a significance value of 0.015 being less than 0.05, it can be inferred that there is a noteworthy difference. Statistical test results of the N-gain score in the intervention group were 50.3% in the Less Effective category, while in the control group was -4.4% in the Ineffective category. Conclusion: There is a significant mean difference between the two groups. The N-gain score test results in the intervention group were higher than control group. It is hoped that the implementation of DSME with the Peer Support Group will be more systematic, sustainable, and focused on changing behavior.